Rainwater Harvesting-Based Water Resources Conservation - I Made Kariyana; Tri Hayatining Pamungkas; Ida Bagus Weda Erlangga (Universitas Diponegoro, 2022)
Denpasar City has an index of population increase worth 2.07% every year. It is feared that this will become a new problem in terms of environmental sustainability, such as the overexploitation of groundwater to meet the community’s water needs. This study aims to support the sustainability of water resources by using Rainwater Harvesting (RWH) as a form of green building planning. The method used in this study is a quantitative descriptive method, which is an analysis method carried out to calculate and describe the scale of RWH in the focus of the system’s effectiveness with the study location in the campus environment of the Ngurah Rai University Denpasar. The results of the study stated that 11 roofs of capture buildings produced rainwater of 1,783,350 litres/year. Another analysis said that this RWH method could cover all water needs, especially water used for flushing toilets. It is stated that the total water deficit of -703,734 litres/year can be subsidized from the entire remaining rainwater harvesting water of 879,624 litres/year. In addition, rainwater harvesting also plays a role as a form of effort to maintain the conservation of water resources and the application of green buildings that are energy efficient and environmentally friendly.